COVID-19 impact on gender-based violence among women in South Africa during lockdown: A narrative review - Ndlovu, Sithembiso; Mulondo, Mutshidzi; Tsoka-Gwegweni, Joyce; Ndirangu, James (African journal of reproductive health, 2022)
COVID-19, first detected in Wuhan, China, in December 2019, was declared a global pandemic by the WHO following the rapid spread of cases worldwide. The pandemic resulted in governments enforcing nationwide lockdowns, halting economic activities except for essential services. The literature search for this review was limited to African peer-reviewed articles and studies published in English between March 2020 and July 2021. EBSCOhost (PubMed, EBSCOhost, APA PsycArticles, APA PsychINFO, Academic Search Ultimate, Africa-Wide Information, Sociology Source Ultimate, CAB Abstracts, CINAHL with full text, and MEDLINE) electronic database platforms and the Google Scholar search engine and bibliographies of identified sources were used to identify studies that are included in the review. 82 studies were identified for this review and 18 were included in the synthesis. Multiple factors contributed to the surge in gender-based violence (GBV) cases in South Africa, including alcohol availability and consumption, job losses, financial dependence, psychological distress, and emotional imbalances. Effective intervention strategies are proposed, calling for more research to better understand women's experiences of GBV during the COVID-19 pandemic.